House prices and employment reallocation: international evidence - Olympia Bover; Juan F. Jimeno (Institute for the Study of Labor (IZA), 2007)
Over the last decade house prices increased remarkably in many countries. However, while in several countries there was an employment boom in the construction sector, in others the share of employment in this sector did not significantly change. In this paper we estimate a model of labor demand in the construction sector, featuring building constraints, which explains many of the international differences in the response of sectoral reallocation of employment to house prices. Countries with more building possibilities (Spain, Sweden and the US) have a high sectoral reallocation of employment, and display larger elasticities of labor demand in the construction sector with respect to house prices than countries that seem to have fewer building possibilities (Belgium, the Netherlands, and the UK). Nevertheless, our estimates imply that, for the whole economy, the elasticity of labor demand with respect to house prices is broadly similar across countries.
Keywords: 330; House prices; labor demand; sectoral reallocation of labor; Immobilienpreis; Beschäftigungseffekt; Arbeitsnachfrage; Bauwirtschaft; Welt